Co-infection and co-localization of Kaposi sarcoma-associated herpesvirus and Epstein-Barr virus in HIV-associated Kaposi sarcoma: a case report - Julius, Peter; Kang, Guobin; Siyumbwa, Stepfanie; Musumali, Jane; Tso, For Yue; Ngalamika, Owen; Kaile, Trevor; Maate, Fred; Moonga, Phyllis; West, John T.; Angeletti, Peter; Wood, Charles (Frontiers in Cellular and Infection Microbiology, 2023)
Kaposi sarcoma (KS), a multifocal vascular neoplasm frequently observed in HIV-positive individuals, primarily affects the skin, mucous membranes, visceral organs, and lymph nodes. KS is associated primarily with Kaposi sarcoma-associated herpesvirus (KSHV) infection. In this case report, we present a rare occurrence of co-infection and co-localization of KSHV and Epstein-Barr virus (EBV) in KS arising from the conjunctiva, which, to our knowledge, has not been reported previously. Immunohistochemistry (IHC), DNA polymerase chain reaction (PCR), and EBV-encoded RNA in situ hybridization (EBER-ISH) were utilized to demonstrate the presence of KSHV and EBV infection in the ocular KS lesion. Nearly all KSHV-positive cells displayed co-infection with EBV. In addition, the KS lesion revealed co-localization of KSHV Latency-Associated Nuclear Antigen (LANA) and EBV Epstein Barr virus Nuclear Antigen-1 (EBNA1) by multi-colored immunofluorescence staining with different anti-EBNA1 antibodies, indicating the possibility of interactions between these two gamma herpesviruses within the same lesion. Additional study is needed to determine whether EBV co-infection in KS is a common or an opportunistic event that might contribute to KS development and progression.